Aplikasi Pelayanan Rumah Susun Berbasis Website (Studi Kasus: Rumah Susun Cinta Kasih Tzu Chi) - Sukrisna Setiawan; Afri Liandy; Mardiansah Mardiansah; Anita Ratnasari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Rumah Susun Cinta Kasih Tzu Chi applies manual service management so that there are several obstacles that hinder the service process for apartment residents, namely, there is no website-based service system that can accommodate complaints or complaints from residents of the apartment. Therefore, the Website-Based "RUSUN" application with the analysis method of Performance, Information, Economics, Control, Efficiency, Service (PIECES) so as to overcome the obstacles that occur and can increase the effectiveness in providing services to residents of flats.